High-power lithium ion batteries based on preorganized necklace type Li4Ti5O12/VACNT nano-composites - Pawlitzek, Fabian; Pampel, Jonas; Schmuck, Martin; Althues, Holger; Schumm, Benjamin; Kaskel, Stefan (Journal of Power Sources, 2016)
Li4Ti5O12 as anode material for high power Li+-ion batteries is very promising due to its unique electronic properties. However, the lack of electronic conductivity as well as the low Li+-ion diffusion coefficient are major drawbacks in achieving high power densities. In this work, therefore, we prepared a nano-composite consisting of vertically aligned carbon nanotube arrays decorated with in-situ grown necklace type Li4Ti5O12 nanoparticles. Owing to this structure the electrodes exhibit outstanding rate performances with specific capacities of 110 mAh g-1 up to 300C and cycling performance with high capacity retention of 97% after 500 cycles at 10C. Thus, the combination of short Li+-ion diffusion distances within Li4Ti5O12 particles, remarkable electronic conductivity by carbon nanotubes directly grown on the current collector as well as a high contact surface area due to an open pore geometry is essential in achieving high power Li4Ti5O12 anodes.
CRIS-Team Scopus Importer:2023-03-20
Keywords: High-power lithium ion batteries; Li; Nano-composite; Nanotube array; Vertically aligned carbon nanotubes (VACNT)